First Extended Catalogue of Galactic bubble infrared fluxes from WISE and Herschel surveys. Issue 3 (15th November 2017) - Bufano, F.; Leto, P.; Carey, D.; Umana, G.; Buemi, C.; Ingallinera, A.; Bulpitt, A.; Cavallaro, F.; Riggi, S.; Trigilio, C.; Molinari, S.
Abstract: In this paper, we present the first extended catalogue of far-infrared fluxes of Galactic bubbles. Fluxes were estimated for 1814 bubbles, defined here as the 'golden sample', and were selected from the Milky Way Project First Data Release (Simpson et al.) The golden sample was comprised of bubbles identified within the Wide-field Infrared Survey Explorer ( WISE ) dataset (using 12- and 22-μm images) and Herschel data (using 70-, 160-, 250-, 350- and 500-μm wavelength images). Flux estimation was achieved initially via classical aperture photometry and then by an alternative image analysis algorithm that used active contours. The accuracy of the two methods was tested by comparing the estimated fluxes for a sample of bubbles, made up of 126 H ii regions and 43 planetary nebulae, which were identified by Anderson et al. The results of this paper demonstrate that a good agreement between the two was found. This is by far the largest and most homogeneous catalogue of infrared fluxes measured for Galactic bubbles and it is a step towards the fully automated analysis of astronomical datasets.